Association of HLA-class II alleles with risk of relapse in myeloperoxidase-antineutrophil cytoplasmic antibody positive vasculitis in the Japanese population - Kawasaki, Aya; Sada, Ken-ei; Kusumawati, Premita Ari; Hirano, Fumio; Kobayashi, Shigeto; Nagasaka, Kenji; Sugihara, Takahiko; Ono, Nobuyuki; Fujimoto, Takashi; Kusaoi, Makio; Tamura, Naoto; Kusanagi, Yasuyoshi; et al. (Frontiers in Immunology, 2023)
Background. Disease relapse remains a major problem in the management of anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV). In European populations, HLA-DPB1*04:01 is associated with both susceptibility and relapse risk in proteinase 3-ANCA positive AAV. In a Japanese population, we previously reported an association between HLA-DRB1*09:01 and DQB1*03:03 with susceptibility to, and DRB1*13:02 with protection from, myeloperoxidase-ANCA positive AAV (MPO-AAV). Subsequently, the association of DQA1*03:02, which is in strong linkage disequilibrium with DRB1*09:01 and DQB1*03:03, with MPO-AAV susceptibility was reported in a Chinese population. However, an association between these alleles and risk of relapse has not yet been reported. Here, we examined whether HLA-class II is associated with the risk of relapse in MPO-AAV. Methods. First, the association of HLA-DQA1*03:02 with susceptibility to MPO-AAV and microscopic polyangiitis (MPA) and its relationship with previously reported DRB1*09:01 and DQB1*03:03 were examined in 440 Japanese patients and 779 healthy controls. Next, the association with risk of relapse was analyzed in 199 MPO-ANCA positive, PR3-ANCA negative patients enrolled in previously reported cohort studies on remission induction therapy. Uncorrected P values (Puncorr) were corrected for multiple comparisons in each analysis using the false discovery rate method. Results. The association of DQA1*03:02 with susceptibility to MPO-AAV and MPA was confirmed in a Japanese population (MPO-AAV: Puncorr=5.8x10-7, odds ratio [OR] 1.74, 95% confidence interval [CI] 1.40–2.16, MPA: Puncorr=1.1x10-5, OR 1.71, 95%CI 1.34–2.17). DQA1*03:02 was in strong linkage disequilibrium with DRB1*09:01 and DQB1*03:03, and the causal allele could not be determined using conditional logistic regression analysis. Relapse-free survival was shorter with nominal significance in carriers of DRB1*09:01 (Puncorr=0.049, Q=0.42, hazard ratio [HR]:1.87), DQA1*03:02 (Puncorr=0.020, Q=0.22, HR:2.11) and DQB1*03:03 (Puncorr=0.043, Q=0.48, HR:1.91) than in non-carriers in the log-rank test. Conversely, serine carriers at position 13 of HLA-DRβ1 (HLA-DRβ1_13S), including DRB1*13:02 carriers, showed longer relapse-free survival with nominal significance (Puncorr=0.010, Q=0.42, HR:0.31). By combining DQA1*03:02 and HLA-DRβ1_13S, a significant difference was detected between groups with the highest and lowest risk for relapse (Puncorr=0.0055, Q=0.033, HR:4.02). Conclusion. HLA-class II is associated not only with susceptibility to MPO-AAV but also with risk of relapse in the Japanese population.